Analysis of the diet in a Spanish prison and the level of perception in a sample of prisoners - AC Varoucha-Azcarate (Sociedad Española de Sanidad Penitenciaria, 2019)
ABSTRACT Introducción: An analysis is carried out of the diet provided at the Quatre Camins prison (Barcelona), where meals were modified in the first quarter of 2017 to provide a healthier diet. Objectives: The new meals are described in relation to the most prevalent chronic and metabolic pathologies in the prison population and it is checked if they correspond to a healthy diet. The food offered at the prison shops and the perception of prisoners regarding prison food are also analysed. Materials and methods: A mixed methodology study was carried out: a) a descriptive analysis of the new food offered by the kitchen service; and b) an analysis of the meals using the Spanish Healthy Eating Index (IASE) as a reference; as well as a description of the most prevalent pathologies in the prison. To determine the prisoners' perceptions, an ad hoc self-completed questionnaire was designed that consisted of four closed Likert questions and four open questions about the perception of prison food. The prisoners who responded to the questionnaire did so voluntarily, anonymously and under informed consent. Results: A sample of 22 prisoners was used. The score according to the IASE is 60.5 points. The assessments of the sample of 22 prisoners regarding quality, quantity and perception of diet as healthy does not reach pass. Discussion: Access to safe water and food meets the requirements for healthiness, quality and quantity regulated by the current Prison Regulation. The results obtained suggest that the diet in the prison "needs changes" according to the IASE.